The deduction of repairs to property in terms of section 11(d) of the Income Tax Act 58 of 1962 - Shirk, Abigail (Department of Commercial Law, 2021)
As the burden borne by the South African taxpayer seems to increase yearly, the prudent taxpayer must embrace the various deductions available to him or her in terms of the Act . In order to do so the taxpayer must understand the ambit of each deduction so that he or she may plan accordingly. A deduction that has for many years granted relief to the weary taxpayer is that contained in Section 1 l(d).